2002
DOI: 10.1080/00288233.2002.9513512
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in methane emission from dairy cows and breeding ewes grazing ryegrass/white clover pasture in New Zealand

Abstract: Daily methane emission from 12 Romney-cross-bred ewes and 10 lactating Friesian dairy cows, rotationally grazed on perennial ryegrass/white clover dominant pastures, was measured during four seasons of a year (September, November, March, and June/July). Methane emission was measured from each animal for 5 consecutive days in each measurement period using the sulphur hexafluoride tracer gas technique. The pastures varied significantly in chemical composition between seasons, generally decreasing in protein, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 22 publications
5
42
0
Order By: Relevance
“…1) or 3 (exp. 2) consecutive days using the SF 6 tracer gas technique as described by Ulyatt et al (2002). Briefly, pre-calibrated permeation tubes were dosed per os into the reticulo-rumen of each animal 7 d prior to the collection of breath samples, to ensure that SF 6 concentration had reached equilibrium in the rumen.…”
Section: Methodsmentioning
confidence: 99%
“…1) or 3 (exp. 2) consecutive days using the SF 6 tracer gas technique as described by Ulyatt et al (2002). Briefly, pre-calibrated permeation tubes were dosed per os into the reticulo-rumen of each animal 7 d prior to the collection of breath samples, to ensure that SF 6 concentration had reached equilibrium in the rumen.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, only very limited information is available about potential seasonal variations of anthropogenic CH 4 sources (other than rice and biomass burning). Ulyatt et al (2010) reported significant seasonal variations of CH 4 emissions from dairy cows, mainly related to the lactation periods of cows. VanderZaag et al (2014), estimating total CH 4 emissions from two dairy farms, found higher CH 4 emissions in autumn compared to spring, mainly due to varying CH 4 emissions from manure management.…”
Section: European Ch 4 Emissionsmentioning
confidence: 99%
“…Ulyatt et al (2010) reported significant seasonal variations of CH 4 emissions from dairy cows, mainly related to the lactation periods of cows. VanderZaag et al (2014), estimating total CH 4 emissions from two dairy farms, found higher CH 4 emissions in autumn compared to spring, mainly due to varying CH 4 emissions from manure management. Besides agricultural CH 4 sources, CH 4 from landfills (Spokas et al, 2011) and waste water may also exhibit seasonal variations, while only small seasonal variations were found for natural gas distribution systems (McKain et al, 2015;Wennberg et al, 2012;Wong et al, 2016; and further references therein).…”
Section: European Ch 4 Emissionsmentioning
confidence: 99%
“…Typically, the arithmetic average of spot measures is used as the estimate of daily methane production (DMP; g CH 4 /day) yet the accuracy and precision of this approach has not been studied. Emission rates are known to change over momentary, diurnal and longer seasonal patterns (Ulyatt et al, 2002;Munger and Kreuzer, 2008;Crompton et al, 2011), requiring representative sampling. If the protocol does not incorporate sampling of emissions at least over the diurnal feeding and activity cycle, a scaling-up coefficient (as used by Garnsworthy et al, 2012) or adjustment factors (such as for animal activity and time spent in each activity as used by Chagunda et al, 2009) may be required to avoid bias in estimating DMP.…”
Section: Introductionmentioning
confidence: 99%